2012
DOI: 10.1021/ct3003942
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Can a Local Coupled Cluster Approach Be in Computing the Activation Energies of Late-Transition-Metal-Catalyzed Reactions with Au, Pt, and Ir?

Abstract: To improve the accuracy of local coupled cluster (LCC) methods in computing activation energies, we propose herein a new computational scheme. Its applications to various types of late-transition-metal-catalyzed reactions involving Au, Pt, and Ir indicate that the new corrective approach for LCC methods can downsize the mean unsigned deviation and maximum deviation, from the CCSD(T)/CBS reference, to about 0.3 and 0.9 kcal/mol. Using this method, we also calibrated the performance of popular density functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
90
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 163 publications
14
90
1
Order By: Relevance
“…For reaction barrier and reaction energy, the correlation analysis results for eight bestperforming functionals with the smallest MUDs(tot) (selected from the MUD data with DFT dispersion correction except the four new Minnesota functionals N12, N12SX, MN12L, and MN12SX) are shown in Figures 2 and 3, respectively. First we can see that the correlations R 2 are at least 0.94 in both activation energy and reaction energy trend analysis, which 95 and late transition metals Rh, 79 Pd, 79 Ir, 79,99 and Pt. 79,99 For early transition metals Zr, M06-2X was found to perform extremely well for C−H activation of σ-bond metathesis mechanism, with an absolute deviation of merely about 0.2 kcal/mol from the reference coupled cluster data.…”
Section: Correlation Analysis For the Trend Performance Of Dftmentioning
confidence: 86%
“…For reaction barrier and reaction energy, the correlation analysis results for eight bestperforming functionals with the smallest MUDs(tot) (selected from the MUD data with DFT dispersion correction except the four new Minnesota functionals N12, N12SX, MN12L, and MN12SX) are shown in Figures 2 and 3, respectively. First we can see that the correlations R 2 are at least 0.94 in both activation energy and reaction energy trend analysis, which 95 and late transition metals Rh, 79 Pd, 79 Ir, 79,99 and Pt. 79,99 For early transition metals Zr, M06-2X was found to perform extremely well for C−H activation of σ-bond metathesis mechanism, with an absolute deviation of merely about 0.2 kcal/mol from the reference coupled cluster data.…”
Section: Correlation Analysis For the Trend Performance Of Dftmentioning
confidence: 86%
“…89 Also, recently H. Chen and co-workers benchmarked the C−H activation of a small methane molecule by Pd, Ir, and Rh pincer complexes that employed several different pincer ligands. On the basis of LCCSD(T) 90 reference data, the benchmark study showed that for the C−H activation step, in terms of mean unsigned deviation (MUD), B3LYP (MUD = 1.17) was the most accurate DFT method followed by B2GPLYP (MUD = 2.20), 91 B2PLYP (MUD = 2.26), 92 and PBE0 (MUD = 2.27). 93 Nonetheless, given that many Pd-, Ni-, Rh-, and Ir-mediated transformations involve bimolecular processes and bear large ligands, the quantitative and qualitative accuracy of energy calculations has in many cases been greatly influenced by dispersive effects.…”
Section: Energymentioning
confidence: 99%
“…Before we discuss the detailed effects of DFT empirical dispersion correction for Mo/W-mediated reactions, it is notable that M06 series DFs are almost not affected by DFT-D3 corrections (the MUDs change by less than 0.09 kcal/mol), which is consistent with the observations in our previous work for other transition metals. [115][116][117]122 This is presumably due to the parametrization of these DFs to account for dispersion interactions to certain extent. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 TPSSh, B2-PLYP, and B2GP-PLYP) have been collected in Table 6.…”
Section: The Effects Of Dft Empirical Dispersion Correctionmentioning
confidence: 99%